Temperature and Water Availability During Maturation Affect the Cytokinins and Auxins Profile of Radiata Pine Somatic Embryos - Moncaleán, Paloma; García-Mendiguren, Olatz; Novák, Ondrej; Strnad, Miroslav; Goicoa, Tomás; Ugarte, María D.; Montalbán, Itziar A. (Frontiers in Plant Science, 2018)
Somatic embryogenesis provides us a potent biotechnological tool to manipulate the physical and chemical conditions (water availability) along the process and to study their effect in the final success in terms of quantity of somatic embryos produced. In the last years, our research team has been focused on the study of different aspects of the somatic embryogenesis in Pinus spp. One of the main aspects affecting somatic embryogenesis is the composition of culture media; in this sense, phytohormones play one of the most crucial roles in this propagation system. Many studies in conifers have shown that different stages of somatic embryogenesis and somatic embryo development are correlated with distinct endogenous phytohormone profiles under the stress conditions needed for the process (i.e. cytokinins play a regulatory role in stress signaling, which it is essential for radiata pine somatic embryogenesis. Based on this knowledge, the aim of this study was to test the effect of different temperatures (18, 23 and 28ºC) and gelling agent concentrations (8, 9, and 10 gL-1) during the maturation stage of Pinus radiata somatic embryogenesis in maturation and germination rates. Parallel, phytohormone profile of somatic embryos developed was evaluated. In this sense, the highest gellan gum concentration led to significantly lower water availability. At this gellan gum concentration and 23ºC a significantly higher number of somatic embryos was obtained and the overall success of the process increased with respect to other treatments assayed. The somatic embryos produced in these conditions showed the highest concentration of iP-type cytokinins and total ribosides. Although, the different conditions applied during maturation of somatic embryos led to different hormonal profiles, they did not affect the ex vitro survival of the resulting somatic plants, where no significant differences were observed.